SANKSI ADMINISTRATIF TERHADAP PPAT ATAS KELALAIAN PENGAWASAN PEMBAYARAN BPHTB DALAM PEMBUATAN AKTA PERALIHAN HAK ATAS TANAH - SRI YUMEINAR SITOMPUL (PREMISE LAW JURNAL, 2016)
Government Regulation No. 37/1998 on PPAT (Official Empowered to Draw up Land Deeds) states that in the case of transferring of title on land and building, PPAT/Notary has the authority to draw up a certificate and validates the rights, and he also has the authority to examine and supervise, as well as to enforce law on the responsibility to pay BPHTB (Income Tax on Land and Building). Article 91 of Law No. 28/2009 on PDRD states that PPAT/Notary oinly has the right to sign the transfer of right certificate on building after the taxpayer has submitted tax quittance. PPAT/Notary who violates the provision on signing certificate (after taxpayer has submitted tax quittance), will be imposed on administrative sanction by paying the fine of Rp.7,500,000 (seven million five hundred thousand rupiahs) for each violation as it is stipulated in Article 93, paragraph 1 of Law No. 28/2009 on PDRD. The problems of the research are as follows: what type of administrative sanction which will be imposed on PPAT/Notary who has violated Article 91, paragraph 1, who has the authority to give the sanction on Article 91, paragraph 1 of Law No. 28/2009 on PDRD, how about fulfilling the principle of justice in imposing the sanction on Article 91, paragraph 1 of Law No. 28/2009 on PDRD, and what legal remedy in getting legal protection for PPAT/Notary about the sanction in Article 91, paragraph 1 of Law No. 28/2009 on PDRD. Keywords: Administrative Sanction, PPAT/Notary, Supervision